Activated Carbon Reduced Nitrate Loss from Agricultural Soil but Did Not Enhance Wheat Yields - Manhattan Lebrun; Sylvain Bourgerie (Nitrogen, 2025)
Wheat requires a high quantity of nitrogen to grow efficiently and produce a high number of nutritious grains (=high yield). The consequences of fertilizer use in uncontrolled conditions are well known, e.g., nitrogen leakage leading to impacts on ecosystems. One solution to reduce these impacts could be activated carbon, which is already used to treat wastewater. In this study, we assessed the efficiency of four activated carbon formulations applied to two agricultural soils in a column leaching test, a greenhouse pot experiment, and a field experiment. In the latter two experiments, wheat was grown with one dose of one selected activated carbon and several nitrogen fertilization conditions. The goal was to find an activated carbon that could stabilize nitrate while improving soil health and thus increase wheat yields. We showed that nitrogen leaching reduction (between 59% and 79% when significant in the column test) was dependent on the raw material used and the activation process. The controlled pot experiment demonstrated that wheat growth was dependent on nitrogen application (60 to 80% increase) and that the activated carbon addition did not enhance yields. Finally, field trials showed that the addition of 1% activated carbon did not result in higher wheat yields compared to those in the non-amended plots in both the absence and presence of nitrogen. In conclusion, although the activated carbon chosen is a strong nitrate-retaining agent, it does not deliver the expected yield gains, probably due to excessive retention, which prevents increased plant growth. More research is needed to improve activated carbon as a fertilizer.